Method for synthesizing hydrogen peroxide from defect-state bismuth tungstate anode through water oxidation and application
By introducing tungsten defective structure into bismuth tungstate material, its catalytic performance is improved, and the problem of low efficiency and high energy consumption of electrocatalytic materials in water oxidation reaction is solved, and high efficiency and low energy consumption of hydrogen peroxide generation and new pollution are achieved. object treatment.
Patent Information
- Application Number
- CN202411492480.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-07
AI Technical Summary
The existing electrocatalytic materials have low catalytic efficiency, high energy consumption and poor stability in water oxidation reactions, resulting in unsatisfactory selectivity and yield of hydrogen peroxide, limiting their application in water treatment and new pollutant treatment.
By introducing bismuth tungstate material with tungsten defective structure, it regulates its electronic structure and active site density, and improves the kinetic performance of water oxidation reaction. The tungsten defective bismuth tungstate electrocatalyst is prepared by alkali etching method, which is used for high efficiency and low energy consumption hydrogen peroxide is produced.
It significantly improves the selectivity and generation efficiency of hydrogen peroxide, reduces by-product generation, extends the service life of the catalyst, enhances the treatment capacity of new pollutants, and is suitable for water treatment and environmental protection applications in low-energy consumption scenarios.
Smart Images

Figure CN119265606A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical water oxidation to produce hydrogen peroxide, and specifically relates to a method and application of synthesizing hydrogen peroxide through water oxidation at a defective bismuth tungstate anode. Background Art
[0002] Hydrogen peroxide (H2O2) is a commonly used strong oxidant, widely used in environmental treatment, medical treatment, industrial synthesis, bleaching and other fields. Its strong oxidizing properties enable it to effectively degrade various difficult-to-treat organic pollutants, such as drug residues, dyes, new pollutants, etc. In addition, hydrogen peroxide can be decomposed into water and oxygen after use, without producing secondary pollution, which meets the requirements of sustainable development and environmentally friendly technology. However, the most important industrial method for producing hydrogen peroxide is still the anthraquinone method, which has a complex process, high energy consumption, is difficult to achieve small-scale decentralized applications, and is not suitable for use in on-site generation scenarios such as water treatment.
[0003] With the increasing demand for environmental protection, researchers have gradually paid attention to the method of directly generating hydrogen peroxide in water through the electrocatalytic water oxidation reaction (WOR). WOR is the process of decomposing water molecules into oxygen or oxides (such as hydrogen peroxide) through electrochemical reactions. The two-electron path (2-electron WOR) can generate H2O2 at a lower potential. Compared with traditional H2O2 production methods, electrocatalytic WOR has the following advantages: (1) Green and environmentally friendly: water is used as the reaction raw material, no organic solvent is required, no harmful byproducts are produced during the reaction process, and hydrogen is produced by the cathode reaction; (2) Simple process: only water, electricity and catalyst are required, and no aeration is required; (3) Applicable scenarios: This method can achieve in-situ generation of H2O2, especially suitable for anaerobic and light-free water treatment scenarios, such as groundwater pollution treatment. However, the current method of preparing hydrogen peroxide by WOR still has many shortcomings: (1) Low catalytic efficiency: The current electrocatalysts used for water oxidation reaction (WOR) to produce hydrogen peroxide (H2O2) have low efficiency and are difficult to efficiently and selectively produce H2O2. Many catalysts tend to produce oxygen through a four-electron pathway (4-electron WOR), resulting in unsatisfactory product selectivity. (2) High energy consumption: Existing electrocatalytic materials often require a high overpotential to drive the reaction, resulting in increased energy consumption, reducing the overall economy and practicality, especially in large-scale or field applications. Low energy efficiency. (3) Poor catalyst stability: Some catalysts are prone to structural damage or electrochemical corrosion during electrocatalytic reactions, and their performance significantly deteriorates after long-term use, limiting their lifespan and feasibility in practical water treatment applications. (4) Limited effect on the treatment of new pollutants: Existing research on the preparation of hydrogen peroxide by water oxidation has limited application in practical water treatment. It can be seen that existing electrocatalytic materials generally tend to produce oxygen in WOR, while the yield and selectivity of H2O2 are low, and many catalysts require a high overpotential to drive WOR, which limits their practical application. Therefore, it is particularly important to develop technologies for preparing hydrogen peroxide with high efficiency and low energy consumption.
[0004] Bismuth tungstate (Bi2WO6) is a material with excellent photoelectrochemical properties. In recent years, it has shown broad application prospects in the fields of photocatalysis and electrocatalysis. Bismuth tungstate as an electrocatalytic material has good stability and high catalytic activity, and is a potential catalyst for efficient H2O2 generation from water oxidation. Studies in recent years have shown that the introduction of defect structures (such as oxygen vacancies, metal defects, etc.) into electrocatalytic materials can significantly enhance the catalytic performance of the materials. Therefore, if suitable defect structures can be introduced into bismuth tungstate materials, it is expected to further improve their electrocatalytic performance, enhance the density of active sites on their surface, and optimize their electronic structure, thereby improving the kinetics of their water oxidation reactions. Summary of the invention
[0005] In order to overcome the above-mentioned shortcomings of the prior art, the present invention proposes a bismuth tungstate electrocatalytic material based on tungsten defects to prepare hydrogen peroxide with high efficiency and low energy consumption, and to be applied to the degradation of new pollutants. 6+ The tungsten defects can enhance the active site density on the catalyst surface and optimize the electronic structure, thereby improving the kinetics of the water oxidation reaction.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides a method for preparing a tungsten-defective bismuth tungstate material, the method comprising the following steps:
[0008] S1. Disperse Bi(NO3)3·5H2O, Na2WO4·2H2O and CTAB in water and stir at room temperature to form a suspension;
[0009] S2, subjecting the suspension of S1 to a hydrothermal reaction, collecting the solid after the reaction, washing and drying it to obtain Bi2WO6;
[0010] S3, adding Bi2WO6 in S2 into alkaline solution, and obtaining bismuth tungstate material with tungsten defects after immersion etching.
[0011] The present invention obtains a bismuth tungstate material with tungsten defects by a simple alkaline etching method, and regulates the performance of the bismuth tungstate material in preparing hydrogen peroxide by electrocatalytic water oxidation through defect construction. The introduction of tungsten defects can adjust the electronic structure of bismuth tungstate, increase the number of its active sites, and then promote the dissociation of water molecules and the formation of active intermediates. The engineered design of this defect structure not only improves the efficiency of in-situ generation of hydrogen peroxide, but also reduces the generation of by-products. It has good application prospects in new pollutant water treatment and green production of hydrogen peroxide.
[0012] Preferably, in step S1, the mass ratio of Bi(NO3)3·5H2O to Na2WO4·2H2O is 2-3:1, the mass ratio of Bi(NO3)3·5H2O to CTAB is 18-20:1, and the material-liquid ratio of Bi(NO3)3·5H2O to water is 0.3-0.7 g:10 mL.
[0013] Preferably, in step S2, the temperature of the hydrothermal reaction is 110-130° C., and the time is 20-30 h.
[0014] Preferably, in step S3, the alkali solution is a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 0.3-0.5M.
[0015] Preferably, in step S3, the material-liquid ratio of Bi2WO6 to sodium hydroxide solution is 0.01-0.02 g:10 mL.
[0016] Preferably, in step S3, the immersion etching time is 0.5-2h.
[0017] The second aspect of the present invention provides a tungsten-defect bismuth tungstate material prepared by the preparation method described in the first aspect.
[0018] The third aspect of the present invention provides the use of the tungsten-deficient bismuth tungstate material described in the second aspect in water oxidation to synthesize hydrogen peroxide and / or degrade new pollutants in water bodies.
[0019] The present invention utilizes tungsten-defective bismuth tungstate materials to produce hydrogen peroxide in electrocatalytic water oxidation, and combines it with advanced oxidation technology for the degradation of new pollutants, thereby providing an efficient and environmentally friendly solution for the production of hydrogen peroxide. This invention utilizes tungsten-defect enhanced bismuth tungstate electrocatalytic materials, which not only achieves efficient generation of hydrogen peroxide, but also expands its application in the degradation of new pollutants. This new material provides a new direction for the development of water treatment technology and is expected to be widely used in the fields of industrial wastewater treatment, domestic sewage purification and environmental remediation.
[0020] The fourth aspect of the present invention provides a method for producing hydrogen peroxide by oxidizing water, specifically: using a three-electrode system, with the carbon electrode loaded with the tungsten-defect bismuth tungstate material described in the second aspect as the anode, with a bicarbonate solution as the electrolyte, an external power supply, and applying voltage to form an electrolysis path to produce hydrogen peroxide through an electrochemical reaction.
[0021] Preferably, the preparation method of the anode is: mixing the defective bismuth tungstate material with the Nafion solution, uniformly coating the obtained suspension on the carbon substrate under high temperature conditions, and then calcining the carbon cloth electrode in an argon atmosphere after drying to obtain an anode loaded with bismuth tungstate.
[0022] More preferably, the material-liquid ratio of defective bismuth tungstate material to Nafion solution is 0.1-0.2 g:1 mL.
[0023] More preferably, the mass concentration of the Nafion solution is 0.2-0.4 g / L.
[0024] More preferably, the coating temperature is 140-160°C.
[0025] More preferably, the argon calcination temperature is 340-360° C., and the calcination time is 25-40 min.
[0026] Preferably, in the three-electrode system, the carbon rod electrode is used as the cathode and the Ag / AgCl electrode is used as the reference electrode.
[0027] Preferably, the concentration of the bicarbonate solution is 1-3 mol / L.
[0028] Preferably, the applied voltage is 2.1-2.9 V vs RHE.
[0029] Preferably, the novel pollutants include but are not limited to ibuprofen.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] Electrocatalytic materials in the prior art tend to generate oxygen through a four-electron pathway, resulting in low selectivity of hydrogen peroxide (H2O2), affecting yield, and the application scenarios of hydrogen peroxide are relatively limited. To this end, the present invention significantly improves the selectivity of the catalyst for generating H2O2 through a two-electron pathway by introducing tungsten defects in bismuth tungstate (Bi2WO6) materials, effectively inhibiting the generation of oxygen. Compared with existing catalysts, the defective bismuth tungstate catalyst of the present invention can achieve a higher H2O2 generation rate at a lower voltage, and the selectivity is significantly improved, reducing the generation of by-products. In general, the defective bismuth tungstate of the present invention has significant improvements in yield, energy consumption, stability, cost, and new pollutant degradation capabilities, solving the problems of low catalyst efficiency, high energy consumption, and instability in traditional WOR technology, especially in the fields of environmental protection and water treatment. It has broad application prospects.
[0032] Specifically, the present invention has the following advantages:
[0033] (1) Improving catalytic efficiency and selectivity: By introducing tungsten defects, the bismuth tungstate material of the present invention can significantly improve the generation efficiency of H2O2 in the water oxidation reaction, while inhibiting unnecessary oxygen generation and improving the selectivity of H2O2.
[0034] (2) Reduce energy consumption: Tungsten defects can effectively regulate the electronic structure of the material, reduce the starting voltage of the catalytic reaction, thereby reducing the consumption of electrical energy and improving overall energy efficiency, making it suitable for use in low-energy consumption scenarios.
[0035] (3) Enhanced catalyst stability: The tungsten-defect bismuth tungstate material of the present invention has higher structural stability, can maintain high activity during long-term electrocatalysis, extend the service life of the catalyst, and meet the needs of industrial or continuous water treatment applications.
[0036] (4) Improving the ability to treat new pollutants: The present invention utilizes H2O2 generated in situ to achieve efficient degradation of new pollutants, thus expanding the application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is the XRD diagram of bismuth tungstate and tungsten-defect bismuth tungstate materials;
[0038] Figure 2 LSV curves of bismuth tungstate and tungsten-defect bismuth tungstate materials;
[0039] Figure 3 It is the hydrogen peroxide production of bismuth tungstate and tungsten-defect bismuth tungstate materials in 2 mol / L potassium bicarbonate solution;
[0040] Figure 4 The hydrogen peroxide production of tungsten-deficient bismuth tungstate material Bi2WO6-1.5 in different electrolytes;
[0041] Figure 5 The removal effect of empty carbon cloth, Bi2WO6 and tungsten-defective bismuth tungstate material Bi2WO6-1.5 on 10ppm ibuprofen solution;
[0042] Figure 6 This is the removal effect of tungsten-defect bismuth tungstate material Bi2WO6-1.5 on 10ppm ibuprofen solution under different voltage conditions. DETAILED DESCRIPTION
[0043] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0044] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0045] Example: Preparation of tungsten-defect bismuth tungstate electrocatalyst
[0046] (1) 0.970 g of Bi(NO3)3·5H2O, 0.330 g of Na2WO4·2H2O, and 0.05 g of CTAB were dispersed in 30 mL of deionized water by ultrasonication at 110 W for 30 min, and stirred at 600 rpm overnight at room temperature to obtain a suspension;
[0047] (2) The suspension was transferred to a 50 mL Teflon liner and subjected to hydrothermal reaction at 120 °C for 24 h;
[0048] (3) collecting the solid after the reaction, washing it with deionized water and anhydrous ethanol three times respectively, and drying it in a 60° C. oven overnight to obtain a bismuth tungstate electrocatalytic material prepared by a hydrothermal method, namely, Bi2WO6;
[0049] (4) Take 20 mg of Bi2WO6 and add it into 20 mL of 0.34 mol / L sodium hydroxide solution, stir for 0.5, 1, 1.5, and 2 h respectively, centrifuge the solution after the reaction, collect the solid, and obtain tungsten-defect bismuth tungstate materials with different etching times, namely Bi2WO6-0.5, Bi2WO6-1, Bi2WO6-1.5, and Bi2WO6-2.
[0050] The XRD results of bismuth tungstate and tungsten-defect bismuth tungstate materials are as follows Figure 1 As shown, it can be seen that the prepared Bi2WO6 and the modified bismuth tungstate materials are consistent with orthorhombic bismuth tungstate (PDF#732020). All samples have diffraction peaks at 28.3°, 32.9°, 47.1°, 55.8° and 58.5°, which are consistent with the characteristic peaks of the (131), (002), (202), (331) and (262) crystal planes in the standard card, and no other diffraction peaks appear, proving that no other impurities are formed. After NaOH etching, the XRD pattern of the catalyst did not change significantly, which shows that the introduction of W vacancies did not affect the crystal structure.
[0051] Test Example 1: Electrochemical Performance Test
[0052] The electrocatalytic performance of Bi2WO6, Bi2WO6-0.5, Bi2WO6-1, Bi2WO6-1.5 and Bi2WO6-2 in Example 1 was tested as catalysts in water oxidation to produce hydrogen peroxide:
[0053] The electrochemical performance test was carried out in a three-electrode electrolysis device by rotating annular disk electrodes, and the electrodes included a working electrode, a counter electrode and a reference electrode. The glassy carbon electrode loaded with Bi2WO6 was used as the working electrode, specifically weighing 5 mg Bi2WO6, adding 100 μL ethanol and 50 μL Nafion solution, dispersing evenly under 110W ultrasonication for 30 minutes, and then taking 10 μL of the suspension and dripping it evenly on the surface of the glassy carbon electrode, and drying it at 60°C to obtain a glassy carbon electrode covered with a Bi2WO6 film. The cathode used a carbon rod electrode as the counter electrode, and the reference electrode used a silver / silver chloride electrode. A solution containing 2 mol / L potassium bicarbonate was injected into the electrolytic cell as the electrolyte solution, and a bias of 1.0-3.0 V vs RHE was applied for electrochemical reaction. In addition, the test methods of Bi2WO6-0.5, Bi2WO6-1, Bi2WO6-1.5, and Bi2WO6-2 were the same as above.
[0054] Result analysis:
[0055] Test LSV curve such as Figure 2 As shown in Figure 2, Bi2WO6-1.5h etched for 1.5h exhibits the smallest overpotential and a larger current density of 10mA / cm-2 The corresponding potential is 2.145V vs RHE, and the overpotential is 385mV, which is close to the theoretical potential of water oxidation to produce hydrogen peroxide (1.76V vs RHE). Compared with the materials after etching for 0.5h and 1h, it shows that the electrochemical activity of Bi2WO6 has been greatly improved after the introduction of an appropriate amount of W cation vacancies. However, compared with the Bi2WO6-2h material, excessive defects will lead to a reduction in electrochemical active sites, so the current density has decreased and the overpotential has increased.
[0056] Test Example 2: Hydrogen Peroxide Production Test
[0057] The performance of Bi2WO6, Bi2WO6-0.5, Bi2WO6-1, Bi2WO6-1.5 and Bi2WO6-2 in Example 1 was tested as catalysts in water oxidation to produce hydrogen peroxide:
[0058] (1) Preparation of carbon cloth anode loaded with catalyst: Weigh 30 mg of Bi2WO6-1.5, add 200 μL of anhydrous ethanol and 100 μL of Nafion solution (mass concentration of 0.3 g / L), mix by ultrasonication, and evenly coat the resulting suspension on a carbon cloth electrode at 150°C and dry. The dried carbon cloth electrode is placed in an argon atmosphere and calcined at 350°C for 30 min to obtain a carbon cloth anode loaded with bismuth tungstate electrocatalyst (carbon cloth anode loaded with Bi2WO6-1.5).
[0059] (2) Test of hydrogen peroxide production: The test was conducted in a three-electrode electrolysis device using an electrochemical workstation. The electrodes included a working electrode, a counter electrode, and a reference electrode. A carbon cloth anode loaded with a catalyst was used as the working electrode, a carbon rod electrode was used as the counter electrode, and a silver / silver chloride electrode was used as the reference electrode. A solution containing 2 mol / L potassium bicarbonate was injected into the electrolytic cell as an electrolyte solution. The potential of the three-electrode system was controlled to 2.5 V vs RHE by the electrochemical workstation at a speed of 60 rpm, and then an electrochemical reaction was carried out at this constant potential. Samples were taken every 10 minutes during the electrochemical reaction.
[0060] (3) Determination of hydrogen peroxide production: The production of hydrogen peroxide was determined by the potassium titanium oxalate method, specifically: 1 mL of the anode solution was taken each time, 0.5 mL of a 3 mol / L sulfuric acid solution was added to the taken solution, and then 0.5 mL of a 0.05 mol / L potassium titanium oxalate solution was added, the solution was quantitatively made up to 5 mL and shaken well, and then allowed to stand for 15 minutes, and then the absorbance was determined at a wavelength of 400 nm with the reagent blank as a reference. The content of hydrogen peroxide was calculated based on the standard curve.
[0061] Result analysis:
[0062] The hydrogen peroxide production curves of bismuth tungstate materials with different tungsten defect etching degrees at the same voltage (2.5V vs RHE) are shown in Figure 2. Figure 3 As shown, the results show that the amount of hydrogen peroxide accumulated in the Bi2WO6-1.5 material etched for 1.5 hours is much higher than that of other samples after 2 hours of reaction, and is twice that of the original unetched bismuth tungstate material, proving that the introduction of appropriate tungsten defects can improve the performance of the material in water oxidation to produce hydrogen peroxide.
[0063] In addition, the 2mol / L potassium bicarbonate solution was replaced with 2mol / L sodium sulfate solution, 2mol / L potassium carbonate solution, and 0.1mol / L buffer solution, and Bi2WO6-1.5 was used as a catalyst to test the hydrogen peroxide production. The preparation method of 0.1mol / L buffer solution is as follows: add 800mL of deionized water to a 1L volumetric flask, then add 16.284g of dipotassium hydrogen phosphate and 0.888g of potassium dihydrogen phosphate, then add deionized water to make the volume 1L, and shake upside down.
[0064] The experimental results are as follows Figure 4 As shown, Bi2WO6-1.5h produced the highest amount of hydrogen peroxide in KHCO3 electrolyte, which is speculated to be HCO3 - May play a buffering role, high concentration of HCO3 - With 2e - H generated during WOR + Combined to maintain the overall pH of the solution. However, it does not work well in buffer electrolytes with similar effects. - With CO3 2- The H2O2 production in the Na2SO4 electrolyte is also unsatisfactory, so it is reasonable to speculate that HCO3 - Get involved in 2e - WOR process and played a key role.
[0065] Test Example 3: A method for in-situ activation of hydrogen peroxide and degradation of new pollution in water
[0066] The Bi2WO6 and Bi2WO6-1.5 in Example 1 were used as catalysts to test their application in in-situ activation of hydrogen peroxide and degradation of new pollution in water.
[0067] (1) Preparation of carbon cloth anode loaded with catalyst: Weigh 30 mg of Bi2WO6-1.5, add 200 μL of anhydrous ethanol and 100 μL of Nafion solution (mass concentration of 0.3 g / L), mix by ultrasonication, and evenly coat the resulting suspension on a carbon cloth electrode at 150°C and dry. The dried carbon cloth electrode is placed in an argon atmosphere and calcined at 350°C for 30 min to obtain a carbon cloth anode loaded with bismuth tungstate electrocatalyst (carbon cloth anode loaded with Bi2WO6-1.5).
[0068] (2) A degradation experiment of new pollution was carried out in a three-electrode electrolysis device using an electrochemical workstation, wherein the electrodes included a working electrode, a counter electrode and a reference electrode, wherein the anode used a carbon cloth loaded with Bi2WO6-1.5 as the working electrode, the cathode used a carbon rod electrode as the counter electrode, and the reference electrode used a silver / silver chloride electrode. 40 mL of a solution containing 2 mol / L potassium bicarbonate and 10 mg / L ibuprofen was injected into the electrolytic cell as an electrolyte solution, and the potential of the three-electrode system was controlled to 2.5 V vs RHE by the electrochemical workstation at a speed of 60 rpm, and an electrochemical reaction was carried out at this constant potential. During the electrochemical reaction, sampling was performed every 10 minutes starting from 0 min. 1.5 mL was sampled each time and the ibuprofen content was detected by high performance liquid chromatography.
[0069] In addition, the carbon cloth electrode loaded with Bi2WO6-1.5 was replaced with a carbon cloth electrode and a carbon cloth electrode loaded with Bi2WO6, respectively, and the degradation test of ibuprofen was carried out in the same way.
[0070] The experimental results are as follows Figure 5 As shown, by comparing the ibuprofen removal results of the three anodes at a constant voltage of 2.5 V vs RHE, it can be seen that when the Bi2WO6-1.5 electrode is used as the anode, the ibuprofen removal performance of the system is the best, and the removal rate can reach more than 80% after 2 hours, which is significantly higher than the other two anodes.
[0071] Test Example 4: Effect of different bias voltages on the degradation performance of activated hydrogen peroxide in new pollution
[0072] The effect of different bias voltages on the degradation of ibuprofen by activated hydrogen peroxide was determined using Bi2WO6-1.5 anode catalyst.
[0073] The degradation experiment of new pollution was carried out in a three-electrode electrolysis device by an electrochemical workstation, wherein the electrodes included a working electrode, a counter electrode and a reference electrode, wherein the anode used a carbon cloth electrode loaded with Bi2WO6-1.5 as the working electrode, the cathode used a carbon rod electrode as the counter electrode, and the reference electrode used a silver / silver chloride electrode. 40mL of a solution containing 2mol / L potassium bicarbonate and 10mg / L ibuprofen was injected into the electrolytic cell as an electrolyte solution, and the potential of the three-electrode system was controlled to 2.1, 2.3, 2.5, 2.7, 2.9V vs RHE by an electrochemical workstation at a speed of 60rpm, and then electrochemical reactions were carried out at these constant potentials. During the electrochemical reaction, sampling was performed every 10min starting from 0min. 1.5mL was sampled each time and the ibuprofen content was detected by high performance liquid chromatography.
[0074] The results of different bias voltages on the degradation of ibuprofen by activated hydrogen peroxide are shown in Figure 2. Figure 6 As shown in the figure, when the bias voltage is 2.1V vs RHE, the effect of activated hydrogen peroxide on degrading ibuprofen is the worst. As the bias voltage increases, the effect of activated hydrogen peroxide on degrading ibuprofen becomes better. When the bias voltage is 2.9V vs RHE, the removal effect of 10mg / L ibuprofen is the best, and the removal rate can reach 95%.
[0075] In summary, the present invention provides a method for preparing a tungsten-defect bismuth tungstate electrocatalyst, that is, on the basis of hydrothermal synthesis of bismuth tungstate, tungsten defects are introduced by a simple alkaline etching method. The method of the present invention has a simple synthesis process, good repeatability, and can be mass-produced. At the same time, the introduction of tungsten defects significantly improves the catalytic performance of bismuth tungstate materials, can effectively promote the selective generation of H2O2, and improves the generation efficiency of H2O2. In addition, the application of water oxidation to prepare hydrogen peroxide technology has been further expanded, so that it can be used in water treatment containing new pollutants such as ibuprofen and other related applications, and has high application prospects and use value.
[0076] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A method for preparing a tungsten-defective bismuth tungstate material, characterized in that: The following steps are involved: S1. Disperse Bi(NO3)3·5H2O, Na2WO4·2H2O and CTAB in water and stir at room temperature to form a suspension; S2, subjecting the suspension of S1 to a hydrothermal reaction, collecting the solid after the reaction, washing and drying it to obtain Bi2WO6; S3, adding Bi2WO6 in S2 into alkaline solution, and obtaining bismuth tungstate material with tungsten defects after immersion etching.
2. The method for preparing a tungsten-defective bismuth tungstate material according to claim 1, characterized in that: In step S1, the mass ratio of Bi(NO3)3·5H2O to Na2WO4·2H2O is 2-3:1, the mass ratio of Bi(NO3)3·5H2O to CTAB is 18-20:1, and the material-liquid ratio of Bi(NO3)3·5H2O to water is 0.3-0.7 g:10 mL.
3. The method for preparing a tungsten-defective bismuth tungstate material according to claim 1, characterized in that: In step S2, the temperature of the hydrothermal reaction is 110-130° C. and the time is 20-30 hours.
4. The method for preparing a tungsten-defective bismuth tungstate material according to claim 1, characterized in that: In step S3, the alkali solution is a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 0.3-0.5M.
5. The method for preparing a tungsten-defective bismuth tungstate material according to claim 1, characterized in that: In step S3, the material-liquid ratio of Bi2WO6 to sodium hydroxide solution is 0.01-0.02 g:10 mL.
6. The method for preparing a tungsten-defective bismuth tungstate material according to claim 1, characterized in that: In step S3, the immersion etching time is 0.5-2h.
7. Tungsten-defect bismuth tungstate material prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the tungsten-deficient bismuth tungstate material according to claim 7 in water oxidation to synthesize hydrogen peroxide and / or degrade new pollutants in water bodies.
9. A method for producing hydrogen peroxide by oxidation of water, characterized in that: A three-electrode system is used, with the carbon electrode loaded with the tungsten-defect bismuth tungstate material of claim 7 as the anode, a bicarbonate solution as the electrolyte, an external power source, and a voltage applied to form an electrolysis path to produce hydrogen peroxide through an electrochemical reaction.
10. The method for producing hydrogen peroxide by water oxidation according to claim 9, characterized in that: The preparation method of the anode is as follows: the defective bismuth tungstate material is mixed with the Nafion solution, the obtained suspension is evenly coated on the carbon substrate under high temperature conditions, and after drying, the carbon cloth electrode is calcined in an argon atmosphere to obtain an anode loaded with bismuth tungstate.